Potentiating intratumoral therapy with immune checkpoint inhibitors: shifting the paradigm of multimodality therapeutics - B.E. Nelson; A. Naing; S. Fu; R.A. Sheth; R. Murthy; S. Piha-Paul (Immuno-Oncology and Technology)
Immune checkpoint inhibitors (ICIs) have revolutionized oncology, yielding remarkable and durable responses in various cancers. However, a significant proportion of patients develop resistance to ICIs. The tumor microenvironment plays a critical role in immunotherapy resistance, characterized by immune cell composition, regulatory factors, and tumor mutational burden. Intratumoral immunotherapy, involving direct injection of immune-activating agents into tumors, holds promise for converting immunologically ‘cold’ tumors into responsive ‘hot’ tumors. This review explores the rationale for combining intratumoral therapies (ITs) with ICIs, highlighting their complementary mechanisms of action and clinical effects. Notable IT approaches include oncolytic viruses, toll-like receptor agonists, and stimulator of interferon gene agonists with ICIs. Overall, combining ITs with ICIs offers a rational strategy to potentiate antitumor immune response and overcome resistance. Further research is needed to optimize the combination strategies, identify biomarkers of response, and establish the safety and efficacy of these novel therapeutic approaches.